EXPERIMANTAL RESEARCHES OF THE CURRENT BURDENING COURSE PLATES ACHIEVEMENTS - Storozhenko, Leonid; Yermolenko, Dmytro; Tegza Іvan (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article presents the experimental study results of flat intercolumn plates loading work peculiarities of the beamless overlapping developed system. The attention is paid to the design of the experimental designs of the bearing structure with the bevelled platforms of suspension on the outer perimeter of the span plates. The technique of performing experimental studies is presented. The conducted researches enabled to establish the nature of deformation and destruction of intercolumn plates as a separate element in the developed system of beamless overlapping. In this case, the magnitude of the compression deformations decreases to the point where the test specimens rest on the supporting blocks. It confirms the assumption of the transfer of load from the spacers to the intercolumnar on the principle of "linear hinge". Attention is paid to the fact that the achievement of the bearing capacity is not accompanied by the process of destruction, but is characterized by significant movements of the flying part of the plate in the vertical plane.